Finding the right path : how far can we go when communicating about the experiences of people with mental illness? - Chong, Catrice Ai Leen. (2009)
Mental illness has always been fascinating. It will continue to be fascinating till the day modern medicine is able to describe in no uncertain terms what causes it, and how to cure it. With the rising rates of mental illness today, the need for communication about mental illness is becoming more pressing. This project is an exploration into articulating mental illness in visual communications. It touches on the boundaries, complexities and dilemmas faced in doing so.